MANAGEMENT LEARNING: AN ANALYTICAL APPROACH TO TEACHING METHODOLOGIES ASSOCIATED WITH COGNITIVE CAPABILITIES - Silva de Souza, Gustavo Henrique; de Miranda Coelho, Jorge Artur Pecanha; Lima Esteves, Gabriel Germano; Esteves da Silva, Thiago Emidio; Sobral dos Santos, Aline Patricia (European Scientific Journal, ESJ, 2013)
The learning within the major universities in the entire world goes through a specific problem: the lack of effectiveness in the teaching-learning process. Thus, in order to develop theories and proposals to improve this process, as part of the management learning; this following article aims to develop a bibliographic analysis that associate teaching methodologies with cognitive capabilities, to create a structural map of teaching activities that guide the learning process in classroom, basing on student characteristics. From this, this study starts from the premise that the learning process should be used as a strategy for planning the teaching-learning process. Through a specific analysis of parsimonious character and theoretically grounded, it is understood a series of learning activities appropriate to cognitive abilities, so that proposed here a functionalist model of teaching and learning that seeks greater usefulness in the transfer of knowledge in classroom.